Short geometry labs : visual and tactile understanding first - Gardella, Francis; Delaware, Richard (Emerald Publishing Limited, 2022)
Much of the content that students study in a high school geometry course is totally new to them. The middle school mathematics curriculum does not contain preparatory work for many of these topics as it does in preparing students for the study of Algebra. The proposed text would be a landmark book giving students the ability to gain some understanding of the content before it is formally addressed in the lesson in the course. While many teachers use initial classroom activities called 'DoNows,' there are no structured materials available to teachers of Geometry for this purpose. When teachers do use them, these activities are constructed by the teachers. The text provides the teachers with such materials and is structured to address what the teachers are about to present to the students.The Labs can also be used for exploration of topics at the middle school level enhancing the program there and giving students a better preparation for their high school Geometry program.
Includes index.
Keywords: Geometry -- Study and teaching (Secondary); Mathematics -- Study and teaching (Secondary); Education -- Teaching -- Subjects -- Mathematics.; Teachers classroom resources and material.; Teaching of reading, writing and numeracy.; Educational: Mathematics and numeracy.; elektronické knihy; electronic books